Reinventing “Many Voices”: MacBride and a Digital New World Information and Communication Order - Kishan Thussu, Daya (Javnost-The Public, 2015)
The MacBride Commission Report was arguably one of the most significant multilateral interventions in the history of international communication. This article charts its emergence at the time of deeply contested Cold War politics, coinciding with the rise of the southern voices in the global arena, led by the non-aligned nations. Thirty-five years after the report's publication, has the global media evolved into a more democratic system, demonstrating greater diversity of views and viewpoints? Despite the still formidable power of US-led western media, the article suggests that the globalisation and digitisation of communication has contributed to a multi-layered and more complex global media scene, demonstrating the “rise of the rest”.